MANAJEMEN PROGRAM UKS DALAM PENDIDIKAN KESEHATAN DI SMAN 1 AWAYAN - Miranti Miranti (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
School Health Efforts are the main channel of health education in schools to improve healthy living skills and shape healthy living behaviors, which will produce optimal student health degrees. The UKS program is implemented through the TRIAS UKS program, namely health education, health services, and fostering a healthy environment. This study aims to determine the management of the UKS program in health education and to find out the obstacles in the management of the UKS program in health education at SMAN 1 Awayan. This type of research is field research with a qualitative descriptive method. The research subjects were UKS coaches, PMR coaches and school principals. Data collection techniques include the results of observations, interviews and documentation. Data analysis techniques by doing data reduction, data presentation and drawing conclusions. The results of the UKS program management research in Health Education at SMAN 1 Awayan has gone well with the health education program covering social service activities, classroom cleaning competitions, health education, health service skills training, school health cadre activities (little doctor, PMR, school pickets) and healthy school competitions. In planning the UKS program in health education, all members of the school are involved, meaning this is not the task of the UKS coordinator, but there are other parties involved, such as the education office, the nearest health center, subdistrict, and the service for women's empowerment and child protection, population control and family planning who assist in that matter. Organizing this in accordance with decisions that have been determined jointly in the meeting forum according to the respective coordinators. Controlling all these activities is carried out every 3 months or at the beginning of the learning year according to the time available. Whereas the obstacles in the management of the UKS Program in Health Education at SMAN 1 Awayan are the UKS rooms and the limited land and school funding to make it.